Chapter L'approccio eco-territorialista alla pianificazione territoriale e il ruolo fondativo degli aspetti patrimoniali - Marson, Anna (Territori, 2023)
Eco-territorialist approach to spatial planning overcomes functional approaches assuming as key references man/nature co-evolution, the diverse components of living, the participation of inhabitants to territorial governance, the territorial context not as the object of planning choices but as a real living subject. The territorial context, a both existing and potential heritage for the settled community, is considered as a fundamental 'actant' in the ecological transition process. The reference to some important contributions for the ongoing redefinition of the theoretical methodological statute of the discipline substantiates the challenge of this alternative approach to planning.